Economic Outcomes and Incidence of Postsurgical Hypotension With Liposomal Bupivacaine vs Epidural Analgesia in Abdominal Surgeries - Margaret Holtz; Nick Liao; Jennifer H. Lin; Carl V. Asche (Journal of Health Economics and Outcomes Research)
**Background:** Epidural analgesia can be associated with high costs and postsurgical risks such as hypotension, despite its widespread use and value in providing opioid-sparing pain management. We tested the hypothesis that liposomal bupivacaine (LB) might be a reliable alternative to epidural analgesia in this real-world study.